Questions, Measures, and Meaning: Interpreting Indicators from the ifo Business Survey - Felix Leiss; Stefan Sauer; Klaus Wohlrabe (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
In addition to the well-known ifo Business Climate Index for Germany, the ifo Business Survey generates a wide range of further indicators based on monthly responses from around 9,000 companies across all major sectors. These indicators capture current business conditions, expectations, constraints, and sector-specific developments, and many have proven to be valuable leading signals for macroeconomic analysis. This paper provides a systematic guide to interpreting these indicators. We explain the main types of survey questions, outline the methods used to transform responses into economically meaningful measures, and highlight key aspects to consider when interpreting results. Practical examples illustrate how the indicators can be applied in economic analysis, policy advice, and business decision-making.
Keywords: C01; C82; C83; O11; 330; ifo Business Survey; business climate; economic indicators; interpretation guide